2020
DOI: 10.3389/fimmu.2020.00653
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical Characterization of Spleen Remodeling in Murine Experimental Visceral Leishmaniasis

Abstract: Background: Visceral leishmaniasis (VL) is caused by Leishmania infantum or L. donovani infection. One of the main problems related to this disease is the emergence of severe clinical forms with a lethality of 5-20%, even while under specific treatment. In humans and other species susceptible to fatal VL, such as dogs and hamsters, the disruption of splenic white pulp (WP) is accompanied by disease progression. Control of VL progression is seen in BALB/c mice, as evidenced by a mild clinical presentation and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Α recent study reported on the displacement of Lti cells from the PALS to the red pulp, supporting their role in maintaining the structural integrity of the spleen ( Fig. 1 S ) [85] . The correlation between increased plasma cell numbers in the red pulp during VL-induced splenomegaly was initially reported in 2008 [65] .…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Α recent study reported on the displacement of Lti cells from the PALS to the red pulp, supporting their role in maintaining the structural integrity of the spleen ( Fig. 1 S ) [85] . The correlation between increased plasma cell numbers in the red pulp during VL-induced splenomegaly was initially reported in 2008 [65] .…”
Section: Introductionsupporting
confidence: 55%
“…Lymphoid tissue inducer (Lti) cells are known to interact with immune and stromal populations, indicating their importance in maintaining the splenic architecture ( Fig. 1 R ) [85] . Α recent study reported on the displacement of Lti cells from the PALS to the red pulp, supporting their role in maintaining the structural integrity of the spleen ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Mice have been proved as a useful model animal to investigate and characterize immune mechanisms/responses and host factors that influence Leishmania infection, identify genes involved in infection, and also predict the functional role of those genes (Nieto et al 2011;Ong et al 2020). However, the clinical course of visceral leishmaniasis in BALB/c mice depends on several factors including Leishmania species, inoculum size, and inoculation route (Carrion et al 2006;de Melo et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…First described almost a decade ago, histocytometry initially mapped resident and migratory dendritic cell niches and their differences in steady state and inflamed murine skin‐draining lymph nodes, suggesting microanatomical differences in endocrine/paracrine signaling and dendritic cell subset chemotaxis [11]. Since then, it has demonstrated spatial reorganization of follicular helper and regulatory T‐cell subsets in response to influenza vaccine [27], and has identified a specialized subpopulation of CD11b + dendritic cells residing in lymphatic endothelium [12], as well as changes in the number and localization of lymphoid tissue inducer (LTi) cells in splenic white pulp in murine leishmaniasis [28].…”
Section: Histocytometry/clearing‐enhanced 3d Imaging (Ce3d)mentioning
confidence: 99%
“…Two commercial platforms, the Hyperion (Fluidigm, Inc, South San Francisco, CA, USA) and MIBIScope (IonPath, Inc, Menlo Park, CA, USA), have increased their presence in research and clinical labs over the past several years. The technical aspects of these platforms have been meticulously described [23,25,28], but important features and differences are reviewed here.…”
Section: Mass Spectrometry‐based Multiplexing (Msm)mentioning
confidence: 99%